Pentingnya Pengelolaan Manajemen Kelas Dalam Pembelajaran (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
The ability to perform classroom management is one of the characterictics of a profesional teacher. Classroom management is needed because students’ attitudes and characters are always changing from time to time. In this regard, the teacher needs to acquire good classroom management ability, so he/she will always be able to guide the students and create an effective and comfortable learning environment which motivates students to learn well and meets the learning goals that have been established.